Problematika Tenaga Perpustakaan Sekolah di SMPN 3 Padang Panjang - Fauruza, Azka; Rahmah, Elva (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2015)
Writing this article aims to describe: (1) problems about school librarian in the SMP N 3 Padang Panjang and; (2) efforts from school librarian in SMP N 3 Padang Panjang overcome the problem. Data were colleted through direct observation, interview with school librarian in the SMP N 3 Padang Panjang and study in library. Analyzing data with descriptively. Based on analyzing the data, we can conclude it – as follows; First, problems from school librarian manage in the SMP N 3 Padang Panjang library were factor from the human being be self were minus the ability from school librarian and then factor from school environment about minus from cooperation between school librarian with school side, haven`t enought fund and haven`t enought outfit or equipment. Second, efforts from school librarian to manage in the SMP N 3 Padang Panjang library were factor from the human being be self were treement from guidance and expand ability from school librarian and then from school environment were build cooperation between school librarian with school side, school side must organize fund and school side must fill outfit or equipment.Keywords : school librarian, guidance, expand ability